Wireless technology for pre-school learning environment - Lam, Yaoming (2015)
Pre-school learning has been very challenging for educators as children typically have short attention span and concentration. To induce tangible user interface in pre-school learning is what motivated this project to be proposed. A Smart box is proposed whereby RFID readers are embedded in it to communicate with tangible objects that also have RFID tags embedded in them to aid in pre-school learning. This Smart box will communicate to a server, preferably an Android device, via Bluetooth Low Energy technology. Wireless technologies are well established and commonly used in a myriad of collaboration activities. Wi-Fi and Bluetooth are the most commonly seen wireless technology in everyday life with home LAN networks and Bluetooth home automation system. This project will explore the new technology of BLE to be the communication medium between the Smart box and the Android device. Implementing BLE on Android will be challenging as there are limited support for BLE as of current stage and this report will not only implement the BLE application but also test the extensibility of this technology judging on the ability to accommodate many slave devices as well as maintaining acceptable data transfer rate. Further development on Android BLE technology should be done and tested when newer versions of Android becomes readily available with more functionality to suit different operation environment.